Analisis Audit Sistem Informasi Pada PT XYZ Menggunakan Framework Cobit 2019 - Muthia Syakirah; Safina Riadi; Dicky Pratama (Journal Of Informatics And Busisnes, 2026)
Information system audit is essential to ensure the effectiveness, security, and alignment of IT systems with a company’s strategic objectives. This study analyzes PT XYZ’s information system using the COBIT 2019 framework, focusing on process capability assessment, governance compliance, and identifying areas for improvement. The research employs a descriptive case study approach, using primary data from interviews and observations, and secondary data from internal documentation and company SOPs. Analysis covers five COBIT 2019 domains (EDM, APO, BAI, DSS, MEA) and maps processes to Enterprise Goals to evaluate strategic alignment. Audit results indicate most domains are at Level 2 (Managed), while BAI and MEA remain at Level 1 (Performed), highlighting the need for improved documentation and monitoring. Recommendations include enhancing process documentation, strengthening IT governance, staff training, implementing SLAs, and conducting regular evaluations. This study provides a foundation for PT XYZ to improve information system capability and IT governance effectiveness.